Battlefield Emotions in Late Antiquity: A Study of Fear and Motivation in Roman Military Treatises - Różycki, Łukasz, author.
1 online resource.
Keywords: Battlefield Emotions in Late Antiquity is a pioneering work, the first to present a comprehensive analysis of fear and motivation on the battlefields of Late Antiquity. By examining military treatises, Łukasz Różycki identifies means of manipulating the morale of soldiers on the same and on opposing sides, showing various examples of military trickery. The book analyzes non-combat properties of equipment, commanders' speeches, war cries, keeping up appearances, and other methods of affecting the human psyche. The book is written in the spirit of new military history and combines the methodology of a historian, archaeologist, and philologist, and also considers aspects of psychology, particularly related to the functioning of groups and individuals in extreme situations.